Ideal Bandgap Organic–Inorganic Hybrid Perovskite Solar Cells - Yang, Zhibin; Rajagopal, Adharsh; Jen, Alex K.‐Y. (Advanced materials (Weinheim), 2017)
Extremely high power conversion efficiencies (PCEs) of ≈20–22% are realized through intensive research and development of 1.5–1.6 eV bandgap perovskite absorbers. However, development of ideal bandgap (1.3–1.4 eV) absorbers is pivotal to further improve PCE of single junction perovskite solar cells (PVSCs) because of a better balance between absorption loss of sub‐bandgap photons and thermalization loss of above‐bandgap photons as demonstrated by the Shockley–Queisser detailed balanced calculation. Ideal bandgap PVSCs are currently hindered by the poor optoelectronic quality of perovskite absorbers and their PCEs have stagnated at <15%. In this work, through systematic photoluminescence and photovoltaic analysis, a new ideal bandgap (1.35 eV) absorber composition (MAPb0.5Sn0.5(I0.8Br0.2)3) is rationally designed and developed, which possesses lower nonradiative recombination states, band edge disorder, and Urbach energy coupled with a higher absorption coefficient, which yields a reduced Voc,loss (0.45 V) and improved PCE (as high as 17.63%) for the derived PVSCs. This work provides a promising platform for unleashing the complete potential of ideal bandgap PVSCs and prospects for further improvement. An ideal‐bandgap (1.35 eV) perovskite (MAPb0.5Sn0.5(I0.8Br0.2)3) is developed with lower non‐radiative recombination states, band edge disorder, and Urbach energy coupled with a higher absorption coefficient, yielding a reduced open‐circuit voltage loss of 0.45 V and improved efficiency of 17.63%. This work provides a promising platform for unleashing the complete potential of ideal‐bandgap perovskite solar cells.